Engineering Macromolecular Trafficking Into the Citrus Vasculature - Calderón-Pérez, Berenice; Ramírez-Pool, José Abrahán; Núñez-Muñoz, Leandro Alberto; Vargas-Hernández, Brenda Yazmín; Camacho-Romero, Abel; Lara-Villamar, Mariana; Jiménez-López, Domingo; Xoconostle-Cázares, Beatriz; Ruiz-Medrano, Roberto (Frontiers in Plant Science, 2022)
The plant vasculature is a central organ for long distance transport of nutrients and signaling molecules that coordinate vegetative and reproductive processes, and adaptation response mechanisms to biotic and abiotic stress. In angiosperms, the sieve elements are devoid of nuclei, thus depending on the companion cells for the synthesis of RNA and proteins, which constitute some of the systemic signals that coordinate these processes. Massive analysis approaches have identified proteins and RNAs that could function as long-range signals in the phloem translocation stream. The selective translocation of such molecules could occur as ribonucleoprotein complexes. A key molecule facilitating this movement in Cucurbitaceae is the phloem protein CmPP16, which can facilitate the movement of RNA and other proteins into the sieve tube. The CmPP16 ortholog in Citrus CsPP16 was characterized in silico to determine its potential capacity to associate with other mobile proteins and its enrichment in the vascular tissue. The systemic nature of CsPP16 was approached by evaluating its capacity to provide phloem-mobile properties to antimicrobial peptides (AMPs), important in the innate immune defense. The engineering of macromolecular trafficking in the vasculature demonstrated the capacity to mobilize translationally fused peptides into the phloem stream for long-distance transport. The translocation into the phloem of AMPs could mitigate the growth of Candidatus Liberibacter asiaticus, with important implications for crop defense; this system also opens the possibility of translocating other molecules to modulate traits such as plant growth, defense, and plant productivity.